The effects of melatonin on plasma homocysteine and oxidative stress parameters in cisplatin-treated rats - Yuece, Abdurrauf; Atessahin, Ahmet; Sahna, Engin; Aksakal, Mesut (Ankara Univ Press, 2007)
The aims of this study were to investigate the effects of cisplatin on nephrotoxicity, plasma homocysteine level and biochemical changes related to oxidative stress and to examine the possible protective role of melatonin administration on these parameters in cisplatin treated rats. In this study, eighteen adult rats were used. The rats were randomly divided into three groups. The first group of rats (control) served as untreated controls and received only physiological saline. The second group of rats (CP) was given cisplatin (7 mg/kg) intraperitoneally. Group third of rats received cisplatin (7 mg/kg) and melatonin (10 mg/kg) (CP+Mel) intraperitoneally. Administration of cisplatin to rats induced a marked renal failure, characterized with a significantly increase in plasma creatinine and urea concentrations. While the plasma malondialdehyde level significantly increased, the plasma homocysteine, glutathione levels and glutathione peroxidase, catalase activities significantly decreased in CP group when compared to control group. Although the administration of melatonin to cisplatin treated animals significantly increased the plasma levels of antioxidant enzymes, and decreased markedly the plasma malondialdehyde level, it has no any significant effect on plasma homocysteine level compared to alone cisplatin group. However, melatonin decreased the plasma homocysteine level compared to the control group. This study indicated that melatonin ameliorated the cisplatin-induced oxidative stress, which had the harmful effect on the renal function. However; it was ineffective on plasma homocysteine level in cisplatin-treated rats.
Keywords: cisplatin; homocysteine; melatonin; nephrotoxicity; oxidative stress; rat